The impact of emotional valence on the spatial scope of visual selective attention - Thitaporn Chaisilprungraung; Poopa Kaewbuapan; Singh Intrachooto; Sarigga Pongsuwan; Sirawaj Itthipuripat (Scientific Reports)
Abstract The brain’s ability to prioritize behaviorally relevant sensory inputs (i.e., targets) while ignoring irrelevant distractors is crucial for efficient information processing. However, the role of emotional valence in modulating selective attention remains underexplored. This study examined how positive and negative emotions alter the spatial scope of visual selective attention using a modified Eriksen Flanker task. Participants viewed an emotional face cue (happy, angry, or neutral) randomly positioned on the screen and then identified the shape of a subsequent neutral target (bowtie or diamond) at the cued location. Adjacent stimuli either matched the target shape (congruent) or differed (incongruent). Results showed that happy faces increased susceptibility to distractors (i.e., a larger incongruency effect), suggesting a broadening of attentional scope, while angry faces reduced susceptibility (i.e., a smaller incongruency effect), indicating a narrowing of focus. Importantly, the magnitude of this emotion-driven attention modulation was negatively correlated with participants’ self-reported levels of psychological distress. Participants with higher stress and depression exhibited weaker attention broadening in response to positive cues. Together, the findings provide behavioral evidence of how emotional valence influences attention scope, offering potential insights into the dynamic interplay between psychological distress, emotional processing, and attention modulation.